Assessment Techniques Corresponding to Scientific Texts in Commercial Reading Programs: Do They Promote Scientific Literacy? - Phillips, Linda M.; Norris, Stephen P.; Smith, Martha L.; Buker, Jodi; Kasper, Chandra (Alberta Journal of Educational Research, 2010)
This research is part of a larger study of commercial reading programs used in Canada in grades 1-6. The specific purposes of the results reported here were to identify and quantify the assessment techniques suggested for the selections that contain scientific content, to show how the assessments differ by grade, to evaluate the nature and quality of the assessments, and to examine the extent to which the assessments help foster scientific literacy. It was found that the assessments occurred in six major forms and employed about a dozen assessment tools that engage students in nearly 20 tasks. Such variety is endorsed in both literacy and science education position statements. The assessments showed some weak trends by grade, but primarily left the purpose of the assessments to teachers’ judgment. The consequence is that teachers probably will choose the assessments for formative rather than summative evaluation, an approach also endorsed by literacy and science education policy statements. Hardly any of the assessments focused on the specificities of learning to read texts that are scientific such as interpreting descriptions of methods and research findings and thus had limited use in promoting this particular aspect of scientific literacy.